INJURY DISORDERS OF NORTH SUMATRA PENCAK SILAT ATHLETES AT THE REGIONAL TRAINING CAMP LEADING UP TO THE XXI NATIONAL SPORTS WEEK - Al Munawar, Ahmad (Universitas Negeri Medan, 2023)
Injury is an abnormality in a person's organs that attacks both the functional and anatomical aspects of the body. Injuries that occur in athletes are usually caused by muscle fatigue from continuous use or due to physical contact that occurs in the competition arena. Injuries are a frightening